Testing the Effect of Big Data Analytics, Cybersecurity Measures, and User Training on Accounting Information System Performance in Start-up Companies in Indonesia - Arief Budi Pratomo (West Science Business and Management, 2023)
Through quantitative research, this study examines the relationship between Big Data Analytics (BDA), Cybersecurity Measures (CSM), User Training (UT), and Accounting Information System (AIS) Performance in Indonesian start-up organizations. Demographic information was gathered from a sample of 135 individuals from a range of business sectors, and data were analyzed using partial least squares (SEM-PLS) and structural equation modeling. The structural model demonstrated a strong positive association between BDA, CSM, UT, and AIS Performance, whereas the measurement model demonstrated excellent validity and reliability. The model's explanatory and predictive capacity was validated by the R2 and Q2 values, and the model fit index showed an adequate fit. The results have applications for enhancing AIS efficacy in the dynamic environment of Indonesian startups